2020
DOI: 10.1155/2020/1764959
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Microbiota Diversity of Patients with Embryonic Miscarriage by Using 16S rDNA High-Throughput Sequencing

Abstract: Embryonic miscarriage severely affects the life quality and physical and mental state of pregnant women. However, the detailed mechanism underlying embryonic miscarriage is not fully understood. This study is aimed at analyzing embryonic miscarriage. We collected samples from 25 normal pregnant women and 25 embryonic miscarriage patients of similar age to analyze microbiota isolated from the vagina. Crude examination of the vagina isolates showed that compared with the control group, 80% of the embryonic misca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 67 publications
(41 reference statements)
0
24
0
Order By: Relevance
“…As previously observed, first trimester miscarriage can be associated with reduced prevalence of Lactobacillus spp. and with changes in the relative abundance of several bacterial genera, including Fam_Finegoldia, Lac_Coprococcus_3, and Lac_Roseburia (Al-Memar et al, 2020;Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously observed, first trimester miscarriage can be associated with reduced prevalence of Lactobacillus spp. and with changes in the relative abundance of several bacterial genera, including Fam_Finegoldia, Lac_Coprococcus_3, and Lac_Roseburia (Al-Memar et al, 2020;Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have investigated the association between vaginal bacterial composition and miscarriage (Zhang et al, 2019;Al-Memar et al, 2020;Fan et al, 2020;Xu et al, 2020). First trimester miscarriage seems to be associated with reduced prevalence of Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown reduced abundance in Lactobacillus spp. and increased α diversity with first trimester miscarriage [ 26 , 27 ]. Lactobacillus -depleted vaginal microbiota also appears to be a risk factor for ectopic pregnancy [ 28 ].…”
Section: Vaginal Microbiota and Reproductive Outcomesmentioning
confidence: 99%
“…First trimester miscarriage associated with reduced prevalence of Lactobacillus spp.-dominated vaginal microbiota classi ed using hierarchical clustering analysis [29]. A study of vaginal microbiota showed that at the genus level, the relative abundance of Fam_Finegoldia and Lac_Roseburia signi cantly differed in the embryonic miscarriage group [30]. In the present study, although there was no signi cant difference in the abundance of dominant bacteria (Firmicutes, Bacteroidetes, Actinobacteria and Proteobacteria) between the two groups, but Actinobacteria and Proteobacteria tended to a higher in RSA patients at the phylum level.…”
Section: Rsa Patients Have Abnormal Gut Microbiotamentioning
confidence: 99%